Financial inclusion and mutual funds investment decision - Mutamimah, Mutamimah; Saputri, Pungky Lela; Indriastuti, Maya (Diponegoro International Journal of Business, 2023)
This study analyses mutual fund investment decisions based on financial inclusion. Multiple regression analysis and the sobel test were used to analyse the data. The population in this study is all mutual fund investors in Central Java, Indonesia. Purposive sampling was used in the sampling method. The results show that financial literacy and financial technology have no effect on mutual fund investment decisions but have a positive influence on financial inclusion, while financial inclusion has a positive effect on mutual fund investment decisions. Thus, financial inclusion can mediate the influence of financial literacy and financial technology on mutual fund investment decisions